Analytical Capabilities of Statistical Methodology for Assessing Threats to Economic Security - D. V. Dianov; E. I. Kuznetsova (Статистика и экономика, 2024)
Subject. Reduction of threats to economic security based on the construction of multifactorial statistical models that quantify the impact of factors on the level of economic crime, in particular, on the scale of material damage from economic crime.   Purposes. Adaptation and application of statistical methodology for complex quantitative assessment of threats to economic security, multifactor modeling of patterns and trends of economic crime.   Methods. Applied methods of multidimensional classification - cluster analysis, correlation and regression, trend models and forecasting.   Results. Statistical modeling was carried out in the context of clusters formed during the study, reflecting the specification of their regions based on the application of statistical methodology for the typologization of the regions of the Russian Federation and the construction of multifactorial statistical models that quantitatively describe the impact of factors on the level of economic crime (the scale of material damage from economic crime).   Conclusions. The results of the conducted research can be used in information and analytical work and activities of departments of internal affairs bodies, public administration bodies to develop directions for reducing economic security risks from criminalization factors. The obtained substantiation of the significance of the factors provides the basis for their inclusion in the dynamic regression model, according to which it is advisable to create short-term forecasts of the crime level of an economic orientation.